New insights from unbiased panel and whole-exome sequencing in a large Chinese cohort with disorders of sex development. Issue 3 (September 2019) - Xu, Yufei; Wang, Yirou; Li, Niu; Yao, Ruen; Li, Guoqiang; Li, Juan; Ding, Yu; Chen, Yao; Huang, Xiaodong; Chen, Yuling; Qing, Yanrong; Yu, Tingting; et al.
Abstract : Context: Diagnosis of non-chromosomal type disorders of sex development (DSD) has long been challenging. There is still no research on overview of a large Chinese DSD cohort. Objective: To determine the etiologic diagnosis through unbiased large-scale panel sequencing and whole-exome sequencing (WES) within a large Chinese DSD cohort. Design: Patients were recruited according to the inclusion criteria of DSD. The applied panel contains 2742 known disease-causing genes, including all known diagnostic genes for DSD. Methods: Targeted panel sequencing (TPS) was performed, and identified candidate variants were verified. Variant pathogenicities were evaluated according to established guidelines. WES was performed for randomly selected negative samples. Results: This study included 125 patients. Seventy-five variants were identified by TPS and 31 variants were reported for the first time. Pathogenic and likely pathogenic variants accounted for 38.7 and 30.7%, respectively. On the basis of clinical certainty, etiologic diagnostic rates of 46.9 and 10.3% were obtained for 46, XY and 46, XX DSD patients, respectively. We reported novel candidate genes ( BMPR1B, GNAS, GHR ) and regions of copy number variants outside the expected DSD genotype–phenotype correlation and determined a founder mutation ( SRD5A2 p.R227Q) in patients with 5α-reductase deficiency. Further WES in randomly selected negative samples identified only one among 14 negative samples as a variant of uncertain significance, indicating that WES did not improve the diagnostic rate. Conclusions: This is the first report of the applying unbiased TPS in a large Chinese cohort of patients with 46, XY and 46, XX DSD. Our findings expand the gene, mutation and phenotype spectra of the rare types of DSD in the Chinese population and provide new insight into the current understanding of the etiologies of DSD.